Surviving girlhood : building positive relationships, attitudes, and self-esteem to prevent teenage girl bullying - Giant, Nikki, 1982-; Beddoe, Rachel, 1978- (Jessica Kingsley Publishers, 2013)
This practical resource is designed to prevent teenage girl bullying by tackling its root causes. Part 1 explores girl bullying and its complexities. Part 2 includes over 60 tried-and-tested activities to help girls aged 11â??16 understand their needs and values, and build self-esteem, positive attitudes, and relationships skills.